“Internal” Problems of Normative Theories of Thinking and Reasoning - Urbańczyk, Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
This paper provides moderate criticism of so-called normative theories of thinking and reasoning. The discussion focuses on the problems of idealization, adequacy, inconsistent yet non-trivial logics, logical omniscience etc. I called them “internal” to the normative approach, because they stem from the very properties of formal systems used to model these two human activities. Some arguments, however, refer to the current theories in cognitive science, including those which are developed within “descriptive” framework.